2019
DOI: 10.2478/dcse-2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities for Development of Emotional Intelligence in Childhood in the Context of Sustainable Education

Abstract: This article deals with systematization of the categories of emotional intelligence, emotional potential and a relationship between emotions and feelings, and emphasizes the importance of a sustainably developed personality in the context of sustainable education (Jovaiša, 2007, 2011). The inward consistency is perceived as an internal human orientation, showing itself in positive relationship with the exterior world and the individual (Pileckaitė-Markovienė, 2002). A person with a strong sense of internal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The sustainability interpretations are available in contexts of different scientific spheres: economics, ecology, psychology, philosophy, art and social sciences (SlunienÎ, 2019;SalÓte, 2015;Fedosejeva et al, 2018). World Commission on Environment and Development (WCED) defined sustainable development as ìÖdevelopment is development that meets the needs of the present without compromising the ability of future generations to meet their own needsî (WCED, 1987, p. 37).…”
Section: Introductionmentioning
confidence: 99%
“…The sustainability interpretations are available in contexts of different scientific spheres: economics, ecology, psychology, philosophy, art and social sciences (SlunienÎ, 2019;SalÓte, 2015;Fedosejeva et al, 2018). World Commission on Environment and Development (WCED) defined sustainable development as ìÖdevelopment is development that meets the needs of the present without compromising the ability of future generations to meet their own needsî (WCED, 1987, p. 37).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional resilience helps children overcome obstacles more easily and take on various challenges without more psychological stress. Moreover, high emotional intelligence means higher levels of empathy, which can lead to less social isolation [23].…”
Section: №1(54)2023 педагогика және психология /педагогика и психолог...mentioning
confidence: 99%
“…However, for family farm members, the social context presents unique challenges, as they are surrounded by both coworkers and family members who may be more alike than different in terms of EI skills. EI develops throughout an individual's lifetime, with their parents serving as the most important reference [17], and as a result, many children in family farm businesses have similar EI skills as their parents [56].…”
Section: Emotional Intelligence and Conflictmentioning
confidence: 99%
“…One possible tool for family farm members is emotional intelligence (EI). EI represents an individual's ability to manage and be aware of their own and others' emotions [11], and plays an important role in organizational sustainability [12][13][14][15][16][17]. Research has shown EI can help individuals build and maintain positive relationships [13,18] and balance work and family responsibilities [16].…”
Section: Introductionmentioning
confidence: 99%